Hubungan Antara Pendidikan Filsafat Dan Keterampilan Berfikir Kritis Siswa Di SDN Tinggar 1 Kec Curug Kota Serang - Irfiyani, Ovi; Silalahi, Suandi (UNTIRTA CIVIC EDUCATION JOURNAL, 2024)
Analyzing the relationship between philosophy learning and students' critical thinking skills at SD Negeri Tinggar 1 Curug District, Serang City is the focus of this research. Philosophy education provides a solid foundation for the development of students' critical thinking abilities, especially from an epistemological perspective. Through a teaching approach oriented towards philosophical conversation, open discussion, and problem solving, students are empowered to independently investigate, analyze, and evaluate knowledge. This research reveals how educators can create a learning atmosphere that supports the development of critical thinking skills by understanding philosophical concepts such as rationalism and empiricism. In addition, the integration of philosophy in the curriculum contributes to the development of critical thinking and reasoning skills necessary to face the challenges of the modern era. This research concludes that philosophy plays an important role in forming students who are not only able to think critically, but also creatively, so that they can become competent individuals and have high competitiveness in society.